64-slice multislice computed tomography: How, when, and why? Part II: Osteoarticular, nervous system, head, and neck - Velán, Osvaldo; Besada, Cristina; Ulla, Marina; Levy, Ezequiel; García Mónaco, Ricardo (Revista del Hospital Italiano de Buenos Aires, 2008)
.